Racial differences in the human endogenous circadian period. - Mark R Smith; Helen J Burgess; Louis F Fogg; Charmane I Eastman (PLoS ONE, 2009)
The length of the endogenous period of the human circadian clock (tau) is slightly greater than 24 hours. There are individual differences in tau, which influence the phase angle of entrainment to the light/dark (LD) cycle, and in doing so contribute to morningness-eveningness. We have recently reported that tau measured in subjects living on an ultradian LD cycle averaged 24.2 hours, and is similar to tau measured using different experimental methods. Here we report racial differences in tau. Subjects lived on an ultradian LD cycle (1.5 hours sleep, 2.5 hours wake) for 3 days. Circadian phase assessments were conducted before and after the ultradian days to determine the change in circadian phase, which was attributed to tau. African American subjects had a significantly shorter tau than subjects of other races. We also tested for racial differences in our previous circadian phase advancing and phase delaying studies. In the phase advancing study, subjects underwent 4 days of a gradually advancing sleep schedule combined with a bright light pulse upon awakening each morning. In the phase delaying study, subjects underwent 4 days of a gradually delaying sleep schedule combined with evening light pulses before bedtime. African American subjects had larger phase advances and smaller phase delays, relative to Caucasian subjects. The racial differences in tau and circadian phase shifting have important implications for understanding normal phase differences between individuals, for developing solutions to the problems of jet lag and shift work, and for the diagnosis and treatment of circadian rhythm based sleep disorders such as advanced and delayed sleep phase disorder.